THE CONTRIBUTION OF THE PROCESSING INDUSTRY TO IMPROVING INDONESIA'S ECONOMY BEFORE AND AFTER THE PANDEMIC - Chodijah; Elvira Rosa; Cindy Indryani; M. David Febrian; Ayu Putri Maharani; Rahma Nurhaliza (CV. Era Digital Nusantara, 2023)
The impact of the covid-19 pandemic has made the economy in Indonesia weakened. we can look at the high levels of unemployment and poverty at that time. The processing industry is one of the sectors that has an important role in driving the economy in Indonesia. This study analyzes the contribution of the processing industry sector in the post-pandemic economic recovery using the Input-Output table analysis method. The Data that the researchers used came from the Central Statistics Agency (BPS). Based on the results of the study, most of the processing industry subsectors have the ability to encourage production growth and improve economic recovery during a pandemic through seven subsectors that have consistently contributed to increasing labor absorption, improving weakening household consumption and weakening people's purchasing power due to the covid 19 pandemic in Indonesia. According to data from the Central Bureau of Statistics (BPS), the food and beverage industry subsector is the largest contributor by generating gross domestic product (GDP) of 1,057,001 27 billion in 2020. Followed by the other six sub-sectors of the processing industry which also contributed a lot to economic recovery. The processing industry is one of the industries that plays an important role in helping the economic recovery of the community in Indonesia after the pandemic.